Technology mergers and acquisitions in the presence of an installed base: A strategic analysis - WANG, Qiu-Hong (Institutional Knowledge at Singapore Management University, 2017)
We study the strategic benefits of M&A when competing IT vendors sell different generations of the same product with different quality. We assume the new product arrives unexpectedly when an installed base of old product exists. We show that the combination of consumers' purchase history and heterogeneity leads to new demand complexity that gives rise to innovative product strategies. We find that shelving the old product is an important motivation for M&A. The acquirer may exercise static or intertemporal price discrimination depending on whether it can exercise upgrade pricing. M&A may speed up or slow down new product consumption, and it can lead to delayed new product introduction in some markets. However, it always increases the acquirer's prot and can sometimes help maximize social welfare. We discuss relevant managerial and policy implications.